An Improved MPC-Based SVPWM Mechanism for NPC Three-Level Z-Source Converters. (12th August 2020) - Hou, Wenbao; Tan, Guojun; Li, Delu
Abstract : Model predictive control (MPC) method has been widely used to reduce the computational complexity of the traditional space vector pulse width modulation (SVPWM). However, for a neutral-point clamped three-level Z-source converter, the performance of the normal MPC strategy would highly depend on the computation processing rate because of the multiple times optimization calculation. In this paper, an improved MPC strategy has been developed, with a voltage prediction being designed to replace the current prediction, the calculation of the roll optimization could be effectively simplified significantly, and then the digital execution efficiency would be improved. Besides, in order to obtain a fixed output harmonic frequency, a combination of this improved MPC and SVPWM has been studied and the shoot-through state insertion for the Z-source also has been analyzed in detail. Lastly, comparison experiments have been carried out to make verification of this improved modulation mechanism.